Photo-realistic 3D model coding in MPEG-4 - Aspert, N.; Ebrahimi, T. (2000 International Conference on Multimedia and Expo, 2000)
The working group ISO/IEC JTC1/SC29/WG11, better known as MPEG (Motion Picture Experts Group), recently adopted a new standard called MPEG-4, which provides solutions for coding of audio-visual objects of a natural and synthetic nature. This paper describes the tools and technologies used in the MPEG-4 standard which allow for efficient compression of photo-realistic three dimensional models. Besides compression efficiency, issues such as streaming, robustness to errors, low complexity and memory usage were taken into account when designing such technologies.